(untitled) (The International Journal for Scientific Research, 2026)
This research paper examines the British role in employing defence diplomacy as a tool of geopolitical influence in the post–Cold War era, particularly in Eastern European countries and former Soviet states. It highlights how this approach contributed to reshaping the military doctrines of those nations within the NATO framework, leading to a strategic polarization with Russia and ultimately fueling the Ukrainian crisis in 2022. The study concludes that British defence diplomacy functions as a dual-purpose instrument—defensive and deterrent from a Western perspective yet perceived as an existential threat from Moscow’s viewpoint.